Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula - Díaz-Rodríguez, Jesús; Gehara, Marcelo; Márquez, Rafael; Vences, Miguel; Gonçalves, Helena; Sequeira, Fernando; Martínez-Solano, Iñigo; Tejedo, Miguel (Zootaxa, 2017)
Parsley frogs (Pelodytes) comprise the only genus in the family Pelodytidae, an ancient anuran lineage that split from their closest relatives over 140 million years ago. Pelodytes is a Palearctic group restricted to Western Eurasia including three extant species: the eastern species P. caucasicus, endemic to the Caucasus area, and two closely related species inhabiting Western Europe: the Iberian endemic P. ibericus and the more widespread P. punctatus. Previous studies based on mitochondrial and nuclear DNA markers have revealed the existence of two additional lineages of Parsley frogs in the Iberian Peninsula, which have been flagged as candidate species. Here, we integrate novel molecular, morphological and bioacoustical data to assess the differentiation of the four western Parsley frog lineages. Species trees and Bayesian population assignment analyses based on nuclear markers confirm previous studies and concordantly delineate four parapatric lineages with narrow hybrid zones. Mitochondrial divergence is low (< 2% pairwise distances in the 16S rRNA gene), in line with previously reported low mitochondrial substitution rates in non-neobatrachian frogs. Based on concordance between mitochondrial and nuclear markers, we conclude that four species of Parsley frogs occur in Western Europe: Pelodytes punctatus, distributed from northern Italy to northeastern Spain; Pelodytes ibericus, inhabiting southern Spain and southern Portugal; Pelodytes atlanticus sp. nov., from the Portuguese Atlantic coast; and Pelodytes hespericus sp. nov., occurring in central and eastern Spain. However, bioacoustical and morphological differentiation of these species is low, with no obvious and qualitative diagnostic characters allowing full species discrimination. Differences in the relative size of metacarpal tubercles exist but this character is variable. Pelodytes ibericus and Pelodytes atlanticus are smaller than the other two species, and P. ibericus has shorter limbs and various distinctive osteological characters. Bioacoustically, the pattern by which two different note types are combined in advertisement calls separates P. hespericus from the remaining species. Despite these differences, we emphasize that the taxonomic status of all four western Parsley frogs requires additional investigation, especially the patterns of genetic admixture across contact zones. While a status of separate species best conforms to the currently available data, alternative hypotheses are also discussed.